Impact of FasL Stimulation on Sclerostin Expression and Osteogenic Profile in IDG-SW3 Osteocytes - Kratochvilova, Adela; Ramesova, Alice; Vesela, Barbora; Svandova, Eva; Lesot, Herve; Gruber, Reinhard; Matalova, Eva (Biology, 2021)
The Fas ligand (FasL) is known from programmed cell death, the immune system, and recently also from bone homeostasis. As such, Fas signalling is a potential target of anti-osteoporotic treatment based on the induction of osteoclastic cell death. Less attention has been paid to osteocytes, although they represent the majority of cells within the mature bone and are the key regulators. To determine the impact of FasL stimulation on osteocytes, differentiated IDG-SW3 cells were challenged by FasL, and their osteogenic expression profiles were evaluated by a pre-designed PCR array. Notably, the most downregulated gene was the one for sclerostin, which is the major marker of osteocytes and a negative regulator of bone formation. FasL stimulation also led to significant changes (over 10-fold) in the expression of other osteogenic markers: Gdf10, Gli1, Ihh, Mmp10, and Phex. To determine whether these alterations involved caspase-dependent or caspase-independent mechanisms, the IDG-SW3 cells were stimulated by FasL with and without a caspase inhibitor: Q-VD-OPh. The alterations were also detected in the samples treated by FasL along with Q-VD-OPh, pointing to the caspase-independent impact of FasL stimulation. These results contribute to an understanding of the recently emerging pleiotropic effects of Fas/FasL signalling and specify its functions in bone cells.
Keywords: osteocyte differentiation; bone; Fas/FasL signalling; caspases; non-apoptotic